Clinical profile and management of patients with acute pulmonary thromboembolism – a single centre, large observational study from India. (February 2021) - Muralidharan, Thoddi Ramamurthy; Ramesh, Sankaran; Kumar, Balakrishnan Vinod; Ruia, Aditya V.; Kumar, Mohan; Gopalakrishnan, Akshaya; Johal, Gurpreet S.; Hooda, Amit; Malhotra, Rohit; Masoomi, Reza; Ramadoss, Mahalakshmi; Subramanian, Vinodhini; et al.
Acute pulmonary thromboembolism is associated with high mortality, similar to that of myocardial infarction and stroke. We studied the clinical presentation and management of pulmonary thromboembolism in the Indian population. An analysis of 140 patients who presented with acute pulmonary thromboembolism at a large volume center in India from June 2015 through December 2018 was performed. The mean age of our study population was 50 years with 59% being male. Comorbidities including deep vein thrombosis, diabetes mellitus, hypertension, and chronic obstructive pulmonary disease were present in 52.9%, 40%, 35.7% and 7.14% of patients, respectively. Out of 140 patients, 40 (28.6%) patients had massive pulmonary thromboembolism, 36 (25.7%) sub-massive pulmonary thromboembolism, and 64 (45.7%) had low-risk pulmonary thromboembolism. Overall, in-hospital mortality was 25.7%. Multivariate regression analysis found chronic kidney disease and pulmonary thromboembolism severity to be the only independent risk factors. Thrombolysis was performed in 62.5% of patients with a massive pulmonary thromboembolism and 63.9% of patients with a sub-massive pulmonary thromboembolism. In the massive pulmonary thromboembolism group, patients receiving thrombolytic therapy had lower mortality compared with patients who did not receive therapy ( p =0.022), whereas this difference was not observed in patients in the sub-massive pulmonary thromboembolism group. We conclude that patients with acute pulmonary thromboembolism in India presented more than a decade earlier than our western counterparts, and it was associated with poor clinical outcomes. Thrombolysis was associated with significantly reduced in-hospital mortality in patients with massive pulmonary thromboembolism.